Peran Pembelajaran PPKn dalam Meningkatkan Kesadaran Hukum Sisiwa di UPT SMPN 2 Mappakasunggu - Anjalita Anjalita; Rismawati Rismawati (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the role of Pancasila and Citizenship Education (PPKn) learning in increasing students' legal awareness at SMPN 2 Mapakasunggu. The approach used was qualitative withHowever, this understanding is not fully reflected in students' daily behavior. Various violations of school rules are still found, such as tardiness, non-compliance with dress codes, and lack of discipline. This indicates that students' legal awareness is still at the cognitive stage and has not been optimally internalized in their attitudes and actions. Factors influencing this condition include learning methods that still find various violations of school rules, such as tardiness, non-compliance with dress codes, and lack of discipline. This indicates that students' legal awareness is still at the cognitive stage and has not been optimally internalized in their attitudes and actions. Factors influencing this condition include learning methods that are still predominantly theoretical, a lack of habituation activities and direct practice, and the influence of the school environment and students' social circles. Therefore, PPKn learning needs to be developed with a more contextual, participatory, and character-oriented approach to continuously improve students' legal awareness.